2017
DOI: 10.1021/acsami.6b16692
|View full text |Cite
|
Sign up to set email alerts
|

Junction-Structure-Dependent Schottky Barrier Inhomogeneity and Device Ideality of Monolayer MoS2 Field-Effect Transistors

Abstract: Although monolayer transition metal dichalcogenides (TMDs) exhibit superior optical and electrical characteristics, their use in digital switching devices is limited by incomplete understanding of the metal contact. Comparative studies of Au top and edge contacts with monolayer MoS reveal a temperature-dependent ideality factor and Schottky barrier height (SBH). The latter originates from inhomogeneities in MoS caused by defects, charge puddles, and grain boundaries, which cause local variation in the work fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 43 publications
1
62
0
Order By: Relevance
“…Additionally, while fringing effects usually increase the effective capacitance, resistive shunts are formed at the edge of Schottky barriers which effectively reduce current [ 81 ]. It should also be noted that decreased capacitance has been reported due to crystalline defects [ 82 ]. Epitaxial growth defects known as carrots (or comet trails) defects, island growth, and step bunching have been directly associated with Schottky rectification [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, while fringing effects usually increase the effective capacitance, resistive shunts are formed at the edge of Schottky barriers which effectively reduce current [ 81 ]. It should also be noted that decreased capacitance has been reported due to crystalline defects [ 82 ]. Epitaxial growth defects known as carrots (or comet trails) defects, island growth, and step bunching have been directly associated with Schottky rectification [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…N‐type Schottky behavior of Au and Pd contacts has been reported both on mono‐ and multilayer MoS 2 . The inhomogeneity of the Au/MoS 2 Schottky barrier has been investigated very recently and attributed to defects, charge puddles, and grain boundaries at the contact . Using density functional calculations, it has been suggested that the metal‐MoS 2 interaction makes the Fermi level pinned at 0.1–0.3 eV below the conduction band edge of MoS 2 for low work function metals, while for high work function metals (≳4.7 eV) the Schottky barrier generally obeys the Schottky–Mott rule .…”
Section: Introductionmentioning
confidence: 99%
“…As we are treating an already hybridized interface, we suspect that the formation of point defects therein, such as migrated interstitials and antisite defects, will serve to trap carriers at the interface and will reduce the crowded injection current at the contact [ 43 ]. This may be empirically confirmed with a combination of low-temperature electrical characterization and capacitance measurements [ 44 – 45 ] in future work.…”
Section: Resultsmentioning
confidence: 58%